ISOLATION PROCESS OF ACID-PRODUCING BACTERIA WITH MODIFIED MEDIA TO OBTAIN ACETOBACTER ACETI IN CASSAVA (MANIHOT UTILISSIMA) FERMENTATION - Zaki, Siti Muzakiyah; Syauqi, Ahmad; Ramadhan, Majida (J-PEN Borneo : Jurnal Ilmu Pertanian, 2023)
Cassava (Manihot utilissima) is a type of high-carbohydrate plant that grows a lot in Indonesia. One of the most common and simple cassava processing is made into tape. One of the microorganisms in yeast is the genus Saccharomyces. Some species of this genus are considered very important in food production materials. One example is Saccharomyces cerevisiae, which is used in winemaking, bread, and beer. This study aims to: study the cassava fermentation process to obtain alcohol compounds as decomposition materials for acid-forming bacteria, knowing the characteristics of acid-forming bacteria in cassava tape fermentation, and getting isolates of Acetobacter aceti bacteria producing acetic acid in the cassava tape fermentation process. This research uses a qualitative descriptive method, with macroscopic, microscopic observations and gram painting on isolates of acid-forming bacteria that have been selected and successfully isolated from cassava fermentation. The results obtained by the colonies showed clear zones and did not show clear zones. Colonies that show clear zones are colonies that produce acid and react with carbonate ions; in the gram test obtained, a genus of bacteria obtained based on the results of isolation on cassava tape, namely some belonging to the genus Acetobacter with gram-negative (colored red) and some genus Lactobacillus with gram-positive (colored purple). The presence of a sour taste on the tape is caused by acid-forming bacteria after the presence of alcohol by the purples Saccharomyces cerevisiae.